(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Miscarriage is a serious health problem across all over the world which is affecting 10-20% of pregnancies. The aim of this was study to compare the efficacy of manual vacuum aspiration with dilatation and curettage in first trimester miscarriages. Methods: It was non-probability consecutive study of 108 women ages between 20 to 35 years, presenting to first trimester with missed miscarriage and gestational age <12 weeks on LMP who were divided into two groups (each 54) group A (D&C) and group B (MVA). This study was conducted at Obstetrics & Gynaecology department, Allama Iqbal Memorial Teaching Hospital and Govt. Sardar Begum Teaching Hospital, Sialkot from June 2024 to December 2024. Results: Mean age was 28.47 ± 4.02 years in group A and 29.01 ± 3.99 years in group B. In group A, mean BMI was 21.98 ± 1.32 kg/m2 and in group B was 22.40 ± 1.70 kg/m2. The gestational age ranged from 5–12 weeks. The mean gestational age in group A was 8.23 ± 1.62 weeks and in group B it was 8.51 ± 1.81 weeks. MVA (85.2%) was more effective than D&C (62.9%). Complication rate after procedure was lesser in group B. Conclusion: Manual vacuum aspiration is more efficient than dilatation and curettage for handling first trimester miscarriages, providing enhanced safety as an added benefit.